Design of the Educational Game Nusantara Adventure - Nasrullah, Nasrullah (Gameology and Multimedia Expert, 2025)
Indonesia is an archipelagic country rich in culture, history, and biodiversity. However, the rapid advancement of globalization has led to a decline in cultural awareness among younger generations. Therefore, an innovative educational medium is needed to engage young learners in exploring Indonesia’s cultural heritage. This study aims to design and develop Nusantara Adventure, an educational game built using Construct 2, with a platformer adventure genre. This game integrates learning and entertainment through mini literacy features and interactions with Book and Guci icons, enabling players to gain insights into Indonesian culture and test their understanding through in-game questions. The development method used is the Game Development Life Cycle (GDLC), which consists of six stages: initiation, pre-production, production, testing, beta release, and release. The Waterfall model is applied, including requirement analysis, design, implementation, testing, and maintenance. The results of this study indicate that Nusantara Adventure is an effective learning tool with interactive gameplay and visually engaging elements, enhancing players’ understanding and appreciation of Indonesian culture. Future improvements may include additional levels and interactive features to further enrich the learning experience.